2004
DOI: 10.1128/iai.72.9.5227-5234.2004
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Major Secreted Yops of Yersinia enterocolitica O:8 to Pathogenicity in the Mouse Infection Model

Abstract: Pathogenic yersiniae (Yersinia pestis, Y. pseudotuberculosis, and Y. enterocolitica) harbor a 70-kb virulence plasmid (pYV) that encodes a type III secretion system and a set of at least six effector proteins (YopH, YopO, YopP, YopE, YopM, and YopT) that are injected into the host cell cytoplasm. Yops (Yersinia outer proteins) disturb the dynamics of the cytoskeleton, inhibit phagocytosis by macrophages, and downregulate the production of proinflammatory cytokines, which makes it possible for yersiniae to mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
154
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 63 publications
8
154
1
Order By: Relevance
“…The immune response to bacteria depends to a large extent on the degree of colonization of the host (colonization of Peyer's patches only vs colonization of liver/spleen). This might account for the poor CD8 T cell response after infection of mice with the yopH, yopM, and yopQ mutants, which are highly attenuated and able to colonize only the gut and Peyer's patches (57). However, because the yopE mutant is comparable in virulence to the yopP mutant (57) differences in colonization are not likely to have influenced this result.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The immune response to bacteria depends to a large extent on the degree of colonization of the host (colonization of Peyer's patches only vs colonization of liver/spleen). This might account for the poor CD8 T cell response after infection of mice with the yopH, yopM, and yopQ mutants, which are highly attenuated and able to colonize only the gut and Peyer's patches (57). However, because the yopE mutant is comparable in virulence to the yopP mutant (57) differences in colonization are not likely to have influenced this result.…”
Section: Discussionmentioning
confidence: 74%
“…Previously we demonstrated that a yopP knockout mutant of Y. enterocolitica was attenuated in an oral mouse infection model (57). In contrast to mice infected with the WA-C(pYV) strain, mice infected with the yopP mutant were able to control infection, eliminating bacteria from spleens and livers by day 12 postinfection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could finally contribute to determine the progression of Yersinia infection in the compromised host. It has been revealed that YopE is required for prolonged colonization of Y. enterocolitica-infected mice (55). This suggests that the cellular effects conferred by YopE primarily play a role in maintaining persistent Yersinia infection, rather than in triggering acute overwhelming disease.…”
Section: Discussionmentioning
confidence: 99%